The Idea of Prevention and Settlement of Human Rights violations in the Field of Natural Resources Based on Local Wisdom - Muhammad Risnain (Universitas Lampung, 2020)
Prevention and settlement of human rights violations based on natural resources is done by establishing good cooperation (synergy) between stakeholders including local governments, community leaders, traditional leaders, religious leaders being one of the keys to avoiding human rights violations in the regions.in the aspect of the settlement of human rights violations can be done by using a settlement mechanism based on local wisdom owned by the region such as the settlement of adat SASAMBO in NTB is an alternative settlement of human rights violations in the future that can be used. So it becomes important to amend Law No. 39 of 1999 concerning human rights violations by including the resolution of human rights violations based on local wisdom in the regions.